2005
DOI: 10.1016/j.ejcts.2004.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary sequestration and aspergillosis

Abstract: Review of literature demonstrates PS fungal colonization to be a rare but recently reported entity (14 cases reported). The observation of four consecutive patients leads us to suggest that PS aspergillosis must be considered in order to evaluate its incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 8 publications
1
11
0
3
Order By: Relevance
“…Nevertheless the cases of asymptomatic, incidentally revealed ILS are controvertial-most authors suggest an early surgery due to possible infectious complications and occult ongoing fungal infection (7,8). This standpoint is in accordance with our results showing lower rate of complications and a trend towards shorter post-surgical hospital stay.…”
Section: A B C Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Nevertheless the cases of asymptomatic, incidentally revealed ILS are controvertial-most authors suggest an early surgery due to possible infectious complications and occult ongoing fungal infection (7,8). This standpoint is in accordance with our results showing lower rate of complications and a trend towards shorter post-surgical hospital stay.…”
Section: A B C Discussionsupporting
confidence: 81%
“…Our own and existing data report Aspergillus sp. to be the most common A B infectious factor to be determined in PS patient; most of patients do not meet the criteria of invasive aspergillosis and have no indication for systemic treatment (4,7,8), the diagnosis of aspergillosis is rather based on pathological stains than microbiological cultures (4). We would suggest to take Aspergillus sp.…”
Section: A B C Discussionmentioning
confidence: 99%
“…19Y21 A recent study has reported the presence of aspergillosis in 4 of 6 patients operated in the last decade in their institute. 21 Four patients in our series presented with the symptoms of infection; however the cultures were sterile probably because of the patients having been started on antibiotics before referral to our institute.…”
Section: Discussionmentioning
confidence: 90%
“…10 Aspergillus fungal organisms have been reported in intralobar sequestrations in the past with 38 reported in the literature. [11][12][13][14][15][16][17][18][19][20][21] Considering that the patient had a history of lung infections, it is possible that the Aspergillus organisms represent a superimposed infection in this case. The fact that fungal organisms have been reported in these prior cases suggests a connection to the tracheobronchial tree and possibly an acquired etiology.…”
Section: Discussionmentioning
confidence: 99%